TERAPI KEBERSYUKURAN UNTUK MENINGKATKAN KESEJAHTERAAN SUBJEKTIF KAJIAN LITERATUR SISTEMATIK - Redualita Christy Kumowal; Marselius Sampe Tondok (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2025)
Background: Subjective well-being is an essential indicator of an individual's happiness, satisfaction, and overall quality of life. Gratitude therapy has emerged as an intervention aimed at improving subjective well-being. Although widely used, evaluating its effectiveness in diverse contexts remains crucial. Objective: This study aims to evaluate the effectiveness of gratitude therapy in enhancing subjective well-being by reviewing existing literature. Method: A systematic literature review was conducted following the PRISMA guidelines. The literature search utilized the keywords “gratitude therapy” AND “subjective well-being” for articles published between 2013 and 2024. Seven studies that met the inclusion criteria were examined. Result: The review found strong evidence from studies conducted both in Indonesia and abroad, indicating that gratitude therapy significantly improves subjective well-being across various participant characteristics. Conclusion: Gratitude therapy is an effective intervention for enhancing subjective well-being. The findings suggest that gratitude therapy can be a viable option for improving well-being, with implications for further research into the psychological factors involved in optimizing subjective well-being.